1992
DOI: 10.1254/jjp.60.269
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Is Essential for ATP-Induced Steroidogenesis in Bovine Adrenocortical Fasciculata Cells.

Abstract: ABSTRACT-The effect of extracellular ATP on steroidogenesis in primary cultured bovine adreno cortical fasciculata cells was investigated. I observed that in the presence of extracellular Ca t+, ATP caused a dose-dependent elevation of intracellular Ca 2+ ([Ca2+];) and induced steroidogenesis concen tration and time-dependently. However, in the absence of extracellular Ca t+, ATP had no effect on steroidogenesis. In the presence of extracellular Ca `+, calmodulin inhibitors inhibited the ATP-induced steroidoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…ATP has been implicated in stimulating steroidogenesis from cortical cells of zona glomerulosa and zona fasciculata [Kawamura et al, 1991;Matsui, 1991;Niitsu, 1992;Jurá nyi et al, 1997]. The occurrence of the P2X 1 receptor subtype in the adrenal cortical cells of the zona reticularis, as found in this study of the guinea pig adrenal gland, may reflect the involvement of ATP in the activities of cells of this region as well.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…ATP has been implicated in stimulating steroidogenesis from cortical cells of zona glomerulosa and zona fasciculata [Kawamura et al, 1991;Matsui, 1991;Niitsu, 1992;Jurá nyi et al, 1997]. The occurrence of the P2X 1 receptor subtype in the adrenal cortical cells of the zona reticularis, as found in this study of the guinea pig adrenal gland, may reflect the involvement of ATP in the activities of cells of this region as well.…”
Section: Discussionsupporting
confidence: 69%
“…It has also been shown that ATP is released from the adrenal capsule and zona glomerulosa region of the gland [Jurá nyi et al, 1997]. Functionally, ATP has been shown to stimulate steroidogenesis from the adrenal zona glomerulosa [Jurá nyi et al, 1997] and fasciculata cells [Kawamura et al, 1991;Matsui, 1991;Niitsu, 1992]. It also facilitates [Chern et al, 1988;Kim and Westhead, 1989] and inhibits [Chern et al, 1987] catecholamine secretion from adrenal chromaffin cells.…”
Section: Introductionmentioning
confidence: 99%
“…Functional studies have shown that ATP can facilitate [12,25] and inhibit [11] catecholamine secretion from adrenal chroma n cells. ATP can also stimulate steroidogenesis from adrenal cortical cells [23,24,27,30]. These observations suggest that ATP receptors located on the adrenal gland cells play important physiological roles in the activity of the gland.…”
Section: Introductionmentioning
confidence: 86%
“…(Matsui 1991) and facilitates steroidogenesis via P2Y receptors (Kawamura et al 1991), which is not inhibited by dihydropyridine (Niitsu 1992). Therefore ATP-induced steroidogenesis might be activated by capacitative Ca 2+ entry.…”
Section: Znmentioning
confidence: 98%
“…We also reported that extracellular adenosine 5 -triphosphate (ATP) facilitates steroidogenesis in BAFC via P2Y receptors (Kawamura et al 1991). Niitsu (1992) (Berridge 1995). Gq protein-coupled receptor agonists stimulate inositol 1,4,5-trisphosphate (IP 3 ) production and subsequent Ca 2+ release from intracellular stores.…”
Section: Introductionmentioning
confidence: 99%